Kenyamanan Termal Ruang Kelas Melalui Building Information Modeling (BIM) - Sakya, Kharista Astrini; Primasetra, Anjar (Universitas Sebelas Maret Surakarta, 2023)
Thermal comfort is determined by the thermal environment, personal factors and other factors. Thermal comfort can affect the state of the user in it, such as in the classroom. The purpose of this study was to identify the thermal comfort of students in the classroom and conduct interventions. Classroom users are final year Interior Design students who use the classroom for approximately 8 hours every day. Therefore, the thermal comfort of the classroom is very important to support the student learning process. The method used is observation and simulation. Making classroom simulations using Building Information Modeling (BIM) technology, then analyzing them through Comfort Temperature and Predicted Mean Vote. The results show that the thermal comfort of students in the classroom is identified as having poor thermal quality. The results of the intervention show that alternative 2 class A is a classroom that has a better quality of thermal comfort than the other alternatives.